Analisis Tekanan Kerja terhadap Kinerja Personil Aviation Security di Bandar Udara Sultan Muhammad Salahuddin Bima, Nusa Tenggara Barat - Meli Urpa Ramdani; Elisabeth Endang Prokosawati (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Sultan Muhammad Salahuddin Bima Airport provides services for security both for passengers, flights, and all areas at Sultan Muhammad Salahuddin Bima Airport. This research aims to find out the work pressures experienced by aviation security personnel during their duties and how aviation security personnel cope with the work pressures they experience so as not to affect performance. This research uses qualitative methods with descriptive qualitative research types. The study used data from documentation, live observations, and interviews conducted with the Commander of Aviation Security and Basic Aviation Security. Sultan Muhammad Salahuddin Bima Airport provides services for security both for passengers, flights, and all areas at Sultan Muhammad Salahuddin Bima Airport. This research aims to find out the work pressures experienced by aviation security personnel during their duties and how Aviation Security personnel cope with the work pressures they experience so as not to affect performance. Urity. Data analysis techniques use data organizing, data management, data verification and interpretation, and inference. The study was conducted at Sultan Muhammad Salahuddin Bima Airport in October 2021. The results of the study conducted by researchers showed that there is a workload felt by aviation security personnel, where the work pressure experienced by aviation security personnel includes pressure from internal Aviation Security and from the passenger side. The way Aviation Security personnel handle feeling pressured at work is to take time off for the next few days. When feeling depressed at work, aviation security personnel take a short break to rest in the Avsec room. Keywords: Performance, Aviation Security, Sultan Muhammad Salahuddin Bima Airport.